2010
DOI: 10.1038/cgt.2010.73
|View full text |Cite
|
Sign up to set email alerts
|

Novel adenovirus-based helper system to support production of recombinant parvovirus

Abstract: Preclinical studies using various cell culture and animal systems highlight the potential of recombinant rodent parvoviruses (recPVs) for cancer therapy. Production of these viruses is, however, not efficient and this hampers the clinical applications of these agents. In this study, we show that the adenovirus genes E2a, E4(orf6) and VA RNA increase the production of recPVs by more than 10-fold and reduce the time of production from 3 to 2 days in HEK293T cells. The helper effects of these genes can be observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Remarkably, both VPA and NaB were found to enhance NS1 transcriptional activity (Fig 3B and Supporting Information Fig S5A). To confirm these results, we infected HeLa cells with a recombinant H-1PV in which the VP gene was replaced with the EGFP encoding gene (recPV-EGFP; El-Andaloussi et al, 2011). VPA was found to enhance NS1-triggered EGFP but not NS1 expression (Fig 3C).…”
Section: Vpa Enhances the Cytotoxic Activities Of The H-1pv Ns1 Proteinmentioning
confidence: 76%
“…Remarkably, both VPA and NaB were found to enhance NS1 transcriptional activity (Fig 3B and Supporting Information Fig S5A). To confirm these results, we infected HeLa cells with a recombinant H-1PV in which the VP gene was replaced with the EGFP encoding gene (recPV-EGFP; El-Andaloussi et al, 2011). VPA was found to enhance NS1-triggered EGFP but not NS1 expression (Fig 3C).…”
Section: Vpa Enhances the Cytotoxic Activities Of The H-1pv Ns1 Proteinmentioning
confidence: 76%
“…The Ad component of the chimera could also assist parvovirus replication in cancer cells at levels other than entry and nuclear trafficking. We have recently shown that specific Ad genomic elements stimulate recombinant PV production by more than 100-fold (10). Similarly, Ad enhances the production of the human B19 parvovirus (14).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to any other recombinant adenovirus vector, the chimera should be produced at high titers, solving the problem of the difficulty related to the production of parvoviruses. Furthermore, we recently reported that expression of adenovirus genomic elements boosted the production of recombinant parvovirus in different cell lines (10). Therefore, we speculated that the Ad-PV chimera may enhance PV replication in cancer cells through the concomitant expression of Ad helper functions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmid DNA is most commonly transferred into cells, but other macromolecules can also be translated inside the cell such as small interfering RNA, oligonucleotides, RNA, and proteins [74]. Transfection may comprise several stages, but formation of pores in the plasmatic membrane, through which extracellular material can penetrate inside the cell, is an obligatory stage [75,76].…”
Section: Helper Plasmids Transfectionmentioning
confidence: 99%